ANALISIS PENGARUH KUALITAS PRODUK, IKLAN MEDIA SOSIAL, DAN HARGA TERHADAP MINAT BELI DI E-COMMERCE: STUDI KASUS PADA PENGGUNA SHOPEE - Muhammad Saifuddin Zuhri; Ahmad Rofiq Santoso, M Akhsin Nailul Author, Rauly Sijabat (CV. ADIBA AISHA AMIRA, 2024)
This study aims to analyze the influence of product quality, social media advertising, and price on purchase intention on e-commerce platforms, with a focus on Shopee users. The survey method is used to collect data from respondents who are active Shopee users. Multiple linear regression analysis is used to test the hypothesis. The study results show that product quality, social media advertising, and price significantly influence Shopee users' purchasing interest. The implications of these findings underscore the importance of these factors in shaping preferences and purchasing decisions in e-commerce environments. This research provides valuable insights for practitioners in developing effective marketing strategies and improving the online shopping experience of Shopee users